The Effect Of The Perkins’ And Blythe’s Model On Mathematical Communication Among Students Of The 5Th Bio Scientific Grade In Mathematics - Kadhim Raheem, Muayad; Fouad Jawad, Lina (Opción, 2019)
The aim of this research is to identify ((the effect of the Perkins’ and Blythe’s model on mathematical communication among students of the 5th bio- sci- entific grade in mathematics)). By verifying the following hypothesis: There was no statistically significant difference (0.05) between the average scores of the experimental group who studied according to the Perkins’s and Bly- the’s model and the average score of the control group students who studied according to the usual method of mathematical communication. For the pur- pose of achieving the goal of the research, the researchers has the following: 1. Prepare instructional plans according to the Perkins and Blaith model steps for the experimental group and others according to the usual method of the control group. 2. Adopting the mathematical communication test prepared by Zina (2013) in a previous study after it was adapted to the students of the research sample by presenting it to some of the arbitrators, which consists of (17) paragraphs. To achieve the research objectives, one of researchers ap- plied the experiment and tested the mathematical communication on a sample of his research which reached (66) students of the 5th bio scientific grade in the preparatory (Mahmoudiya scientific boys) distributed in a simple random way between the experimental and control groups (34) students in the exper- imental group And 32 in the control group for the academic year (2018 - 2019). The two groups were rewarded with (age of time, previous collection of mathematics, in- telligence and mathematical communication). The data were then analyzed using the TI test of two equal independent samples, the results showed a statistically significant difference at (0.05) between the average scores of the experimental group and the average score of the control group students in the sports communication test and for the experimental group In light of the findings of the researchers, they made a number of recom- mendations and proposals for research and study.